A gender-based study of twelve (12) West Visayan Folktales - Centino, Michael Angelou E.
The main thrust of this study is a gender-study of selected West Visayan folktales; with this study we will be able to understand how gender works in the society and how these folktales reflect this condition as well as they counter-act. From this study, four points are observed in the selected West Visayan folktales. First, men follow stiff masculine guidelines, defiance of which leads them to conflict with other men. Second, female characters in the West Visayan folktales are considered as the ?Other? since they take only secondary role to men as imposed by the Western or Spanish standard. Women are used as rewards for the heroic pursuits of men. Third, stereotypes and non-stereotypes representations are evident. Men are expected to be strong in all aspects, and any transgression of this standard causes trouble to the characters. Men are the saviours of women characters. Women are expected to obey their father and husband. In all the folktales used in this study, women are expected to marry or to be married. Fourth, as Spanish with her patriarchal society colonized the Philippines, she expected that men should act like them, the colonizers and women patterned their conduct to women of the motherland (Mananzan, 50). To conclude, in the twelve (12) West Visayan folktales male domination is prevalent, but there are also exceptions where some women rebel or fight back. The term ?gender ambivalence? is coined where the issue of power among genders is not just that of the dominant over the subordinate, but rather an ?ambivalence? where both genders continue to search for their status or place in the society as best exemplified in these folktales. As seen in the folktales, both genders are actually victims of the patriarchal set up.